Implementasi Program Keluarga Harapan Di Kecamatan Tamalate Kota Makassar - Clara Dheby; Abdul Kadir Adys; Muhammad Idris (Department of Public Administration, Muhammadiyah University of Makassar, 2017)
The objective of this research is to know the implementation of expectation family program In Tamalate sub-district of Makassar City. This research is qualitative and the type is phenomenology. The data is obtained by interview, observation, and documentation. The source of data is primary and secondary data. The informant involved in this research is ten informants. A technique of data analysis pervades reduction of data, presentation of data, conclusion, and verification. The legality of data pervades source triangulation, technical triangulation, and time triangulation.The result of this research reveals that Expectation Family Program in health field in Tamalate sub-district has applied digital financial service and health facility providing well. The Expectation Family Program in education field of Tamalate sub-district is not maximal yet, in particular on activation of illiterate children and home providing.Keywords : Implementation of policy, Expectation Family Program Tujuan penelitian ini adalah untuk mengetahui implementasi Program Keluarga Harapan di Kecamatan Tamalate Kota Makassar. Jenis penelitian adalah kualitatif dan tipe penelitian adalah fenomenologi. Data diperoleh melalui wawancara, observasi dan dokumentasi. Sumber data penelitian adalah data primer dan sekunder. Jumlah informan penelitian adalah 10 orang. Teknik analisis data meliputi reduksi data, penyajian data serta penarikan kesimpulan dan verifikasi. Pengabsahan data meliputi triangulasi sumber, triangulasi teknik dan triangulasi waktu. Hasil penelitian menujukkan bahwa PKH bidang kesehatan di Kecamatan Tamalate telah melaksanakan dengan baik layanan keuangan digital dan penyediaan fasilitas kesehatan. PKH bidang pendidikan di Kecamatan Tamalate belum memaksimalkan Pengentasan anak buta huruf dan penyediaan rumah singgah. Kata kunci : Implementasi Kebijakan, Program Keluarga Harapan (PKH)